Exploring the Factors Affecting Organisational Image: Implications for State-Owned Entities - Ahmed, Ammar (International Journal of Psychosocial Rehabilitation, 2020)
Organisational image is crucial to attract and retain talented individuals with enhanced engagement and commitment. Purpose of current study is to explore the factors affecting organisational image in purely state- owned organizations working in capital of Punjab, Pakistan. Organisations are forced to build a positive image after the development of concepts like environmental protection, corporate social responsibility and ethical climate in order to attract and engage talented employees. For this study 250 closed-ended questionnaire were distributed among employees of three different wings of Pakistan audit department using Partial Least Square Structural Equation Modeling (PLS-SEM) to test the proposed hypothesis. The findings of the study depict that ethical climate, corporate social responsibility (CSR) and environmental friend lines play vital role in developing positive organisational image. In Pakistan, the work on said variables is not sufficient and public sector organizations are perceived as incompetent, corrupt and crooked not only by natives but also international communal as well. Hence, this paper provides practical implications for employers in public sector to affectively address the factors that leads to positive organisational image.